Speech therapy in the feminization of voice in transsexuals: bibliographic review - Gómez-Raya, Alejandra (Revista de Investigación en Logopedia, 2018)
Transsexualism is a disorder in which the physiological sex and the gender of a person are mismatched. Transgender people feel the desire to belong to the sex with which they actually identify and this leads them to perform certain actions to change their appearance. The transsexual woman will not achieve the feminization of her voice through the hormonal treatment, being her options: vocal cords surgery and/or speech therapy intervention. The objective of this review is to expose relevant aspects and provide wide information on speech therapy work in the treatment of the feminization of the voice in transsexuals from man to woman as a single treatment not complementary to surgical intervention. To carry out a descriptive bibliographic review, the search for scientific articles in the secondary sources PubMed and Scopus are carried out. Using a qualitative methodology, a list of 25 articles is obtained from each of them. This is checked with filters and inclusion and exclusion criteria, resulting in a list of 7 final articles. Regarding the results, all the articles conclude with positive results of the vocal therapy in transsexual women, especially emphasizing the objectives related to the increase of the fundamental frequency and the increase of the forming frequencies. In conclusion, there is enough information to show that speech therapy can be effective in the feminization of voice in transsexual population. However, the limited number of articles hinder universal generalizations.